A Randomized, Controlled Clinical Trial of a Dermocosmetic Containing Vichy Volcanic Mineralizing Water and Probiotic Fractions in Subjects with Rosacea Associated with Erythema and Sensitive Skin and Wearing Protective Masks - Berardesca E; Bonfigli A; Cartigliani C; Kerob D; Tan J (Dove Medical Press, 2023)
Enzo Berardesca,1 Adriana Bonfigli,2 Claudia Cartigliani,2 Delphine Kerob,3 Jerry Tan4 1Phillip Frost Department of Dermatology, University of Miami, Miami, FL, USA; 2Clinical Evaluations, ISPE, Milano, Italy; 3International Scientific Affairs, Cosmetic Active International, Levallois-Perret, France; 4Department of Medicine and Windsor Clinical Research Inc Western University, Windsor, ON, CanadaCorrespondence: Enzo Berardesca, Phillip Frost Department of Dermatology, University of Miami, Miami, FL, USA, Tel +393486962500, Email berardesca@berardesca.itPurpose: Rosacea is a common facial dermatosis, with flares induced by exposome factors. M89PF containing Vichy mineralizing water, probiotic fractions, hyaluronic acid, niacinamide and tocopherol repairs the skin barrier and reinforces skin defences against exposome factors. This study assessed the benefit of M89PF in subjects with rosacea associated with erythema and sensitive skin during the Covid-19 pandemic using protective face masks.Methods: M89PF was compared to usual skin care in a randomized, split-face study, for 30 days in subjects with rosacea associated with erythema and sensitive skin. Clinical evaluations included erythema, desquamation, skin tightness, dryness, burning sensation, itching, stinging, stinging test, and local tolerability. Instrument evaluations included erythema, skin hydration and TEWL. Subject satisfaction was also assessed.Results: Erythema significantly improved with M89PF at both time points (p< 0.01 at D15, and p< 0.001 at D30). Skin sensitivity assessed by the skin stinging test improved significantly (p< 0.01) with M89PF at D30, compared to baseline and usual skin care. Skin erythema, tightness, dryness, hydration and TEWL significantly improved (p≤ 0.05) with M89PF at D15 and D30, versus baseline and the untreated side. Subjects were highly satisfied with M89PF at D15 and D30. Tolerance was very good in all subjects.Conclusion: In subjects with rosacea, M89PF significantly reduces erythema, skin tightness, dryness and TEWL, and improves skin hydration and skin sensitivity, even when using protective masks. M89PF is well tolerated and received high satisfaction ratings.ClinicalTrials.gov. No: NCT05562661.Keywords: rosacea, skin barrier, exposome, erythema, sensitive skin